VD_FINDINFO Décision / 2014 / 345 vom 7. Februar 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, DÉFENSE D'OFFICE, COMPLEXITÉ DE LA PROCÉDURE | 132 al. 1 let. b CPP (CH), 132 al. 2 CPP (CH), 132 al. 3 CPP (CH), 132 CPP (CH)